(untitled) (Journal of Management and Social Sciences, 2020)
The purpose of this study was to examine the impact of strategic planning on firm performance in the banking industry using First Bank as case study. The specific objectives of the study were to determine the effect of organisation objective on employee turnover, ascertain the effect of long range plan on business survival and analyse the effect of strategic implementation on employee turnover. The study adopted a descriptive research design. Fifty-six questionnaires were administered to the top management in which fifty-six were collected. The data was then presented using frequency tables. The data was analysed using regression analysis. The findings were that there were statistically significant effects of organisation objective on employee turnover, significant effect of long range plan on business survival and significant effect of strategic implementation on employee turnover in First Bank Nigeria Plc, Osun State. The findings recommended that companies should look into the aspects of organisation objective, long range plan and strategic implementation practice put in-place in the organisation as it helps to improve employee performance and turnover.